Extracellular lipidome change by an SGLT2 inhibitor, luseogliflozin, contributes to prevent skeletal muscle atrophy in db/db mice. Issue 1 (2nd December 2021) - Bamba, Ryo; Okamura, Takuro; Hashimoto, Yoshitaka; Majima, Saori; Senmaru, Takafumi; Ushigome, Emi; Nakanishi, Naoko; Asano, Mai; Yamazaki, Masahiro; Takakuwa, Hiroshi; Hamaguchi, Masahide; Fukui, Michiaki
Abstract: Background: Diabetes mellitus increases the excretion of urinary glucose from the renal glomeruli due to elevated blood glucose levels. In the renal tubules, SGLT2 is expressed and reabsorbs the excreted urinary glucose. In the pathogenesis of diabetes mellitus, glucose reabsorption by SGLT2 is increased, and SGLT2 inhibitors improve hyperglycaemia by inhibiting this reabsorption. When urinary glucose excretion is enhanced, glucose supply to skeletal muscle may be insufficient and muscle protein catabolism may be accelerated. On the other hand, SGLT2 inhibitors not only ameliorate hyperglycaemia but also improve fatty acid metabolism in muscle, which may prevent muscle atrophy. Methods: Eight‐week‐old male db/m mice or db/db mice were fed a standard diet with or without the SGLT2i luseogliflozin (0.01% w/w in chow) for 8 weeks. Mice were sacrificed at 16 weeks of age, and skeletal muscle and serum lipidomes, as well as skeletal muscle transcriptome, were analysed. Results: Administration of SGLT2i led to not only decreased visceral fat accumulation ( P = 0.004) but also increased soleus muscle weight ( P = 0.010) and grip strength ( P = 0.0001). The levels of saturated fatty acids, especially palmitic acid, decreased in both muscles ( P = 0.017) and sera ( P = 0.041) upon administration of SGLT2i, while the content of monosaturated fatty acids, especially oleic acid, increased in both muscle ( P < 0.0001) and sera ( P = 0.009). Finally, the accumulation of transcripts associated with fatty acid metabolism, such as Scd1, Fasn, and Elovl6, and of muscle atrophy‐associated transcripts, such as Foxo1, Mstn, Trim63, and Fbxo32, decreased following SGLT2i administration. Conclusions: Intramuscular fatty acid metabolism and gene expression were influenced by the extracellular lipidome, which was modified by SGLT2i. Hence, secondary effects, other than the hypoglycaemic effects of SGLT2i, might lead to the alleviation of sarcopenia.